(untitled) (Revista NUPEART, 2023)
Briefly, this article presents the investigation I developed named, "Houses as museums: affective narratives of Visual Arts teachers". More specifically, it presents the topics rela- ted to the methodological aspects of this process, which I was able to talk about to the students of the Professional Master in Arts/ProfArtes of the Instituto Federal de Goiás/IFG twice, thus collaborating with their training processes. In these meetings, the topics discussed varied from the writing of the thesis to the effects of the Covid-19 pandemic and the approval of the National Common Curricular Base/BNCC in our professional and personal daily lives.